Migration theories and development: a focus on push & pull factors of Filipino migrants - Peralta, Eric Paul; Ancho, Inero; Pelegrina, Daisy (Faculty of Administrative Science and Policy Studies, 2024)
Migration has been an integral part of the lives of Filipinos. It is a phenomenon that has already been existing for several centuries and is motivated by various factors. For this systematic review of related literature, the researchers aim to determine the prominent push and pull factors that influence Filipino international migration from the year 2009 to 2019 as well as to analyze the trends of the socio-demographic characteristics of OFWs or the Overseas Filipino Workers through the years. Everett Lee’s (1966) push-pull theory was used by the researchers to determine the push factors that encourage Filipinos to leave their homes and migrate to another country as well as the pull factors that attract Filipinos to migrate and work in their chosen country of destination. Several related pieces of literature found through the Google and Google Scholar search engines were acquired for this systematic review including data on the population of OFWs based on their socio-demographic aspects. The collected data exhibited that the factors which encourage Filipinos to migrate and work overseas from 2009 to 2019 remained similar through the years. Studies revealed that OFWs are mainly motivated by economic push and pull factors, including unemployment, income, and job opportunities while a study also indicated social factors that are focused on personal development as well as family and friends who also influence the migrant’s decision to move to another country. The researchers were able to conclude that based on the acquired data from studies within the years 2009 to 2019, the factors which encourage Filipinos to migrate and work overseas remained similar through the years. Economic issues of unemployment, income inequalities, and limited job opportunities continued to prevail in the Philippines. Further,, the number of OFWs continued to increase which implies that sustained development in terms of employment, income, and job opportunities, did not occur within those years.